COLLABORATIVE GOVERNANCE SEBAGAI INOVASI KEBIJAKAN STRATEGIS (STUDI REVITALISASI KAWASAN WISATA CAGAR BUDAYA BANTEN LAMA) - Sururi, Ahmad (Faculty of Humanities, Diponegoro University, 2018)
The complexity of the problems faced in the revitalization of Banten Lama cultural sanctuary is the problem of relocation of street vendors incorporated in the Kerosene Traditionist Association of Surosowan Banten Lama, the target of development (revitalization) of infrastructure that has not been achieved and the harmonious cooperation between stakeholders. The purpose of this research is to identify the priority and strategic issues and to develop the innovative model of Collaborative Governance based policy on the Revitalization study of Banten Lama Reserve Tourism Area. The research method used is qualitative descriptive approach with data collection technique through interview and observation and searching various sources and literature both from government documents and news media print and electronic, journal and books related to collaborative governance, policy innovation and revitalization Banten Long. The result of this research is the identification of priority and strategic issues of Revitaliasi Policy of Banten Lama Reserve Tourism Area namely bureaucratic structural dimension, socialization of revitalization and relocation of street vendors incorporated in Paguyuban Keragang Surososwan Banten Lama Traders. Furthermore, the development of innovative governance policy innovation model and revitalization stages include four components, namely the initial conditions consisting of identification of existing conditions, resources, basic considerations and economic political will; the second component is a commitment that includes processes and outcomes, beliefs, common understanding and internal / external legitimacy; the third component is institutional design consisting of structure and procedure, leadership and form of cooperation process; and the fourth component is the final condition that includes follow-up and sustainability.